EFEKTIVITAS TEKNIK ROLE PLAYING DALAM BIMBINGAN KELOMPOK UNTUK MENGURANGI PERILAKU BULLYING SISWA SMPN CAMPLONG- SAMPANG - M Alven Pratama; Moesarofah Moesarofah (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
Tthis study aims to evaluate the effectiveness of the role-playing technique in group counseling to reduce bullying behavior among students’ at SMPN 1 Camplong-Sampang. Bullying is a serious issue in education settings that can negatively impact students’ psychological and social development. Data indicate that indonesia ranks high in bullying cases, with 41.1% of students’ reporting having been victims. The role-playing method was chosen for its ability to enhance interpersonal communication and empathy among students’. Through this approach, students are invited to act in situations reflecting bullying experiences, allowing them to understand the impact of such behaviors both as perpetrators and victims. This research employed a quasi-experimental design with pre-test and post-test to measure changes in students’ behavior after the intervention. The analysis results showed a significant improvement in awareness and a reduction in bullying behavior among students’ who participated in group counseling sessions using the role-playing technique. The wilcoxon test results indicated a significant difference between the pre-test and post-test scores in the experimental group, with an Asymp. Sig. (2-tailed) valiue of 0.11 (p < 0.05). This finding demonstrates that the role-playing technique in group counseling is effective in reducing bullying behavior among students’ at SMPN Camplong-Sampang.